2014
DOI: 10.1128/iai.01028-13
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Intradermal Infection with Trypanosoma congolense Leads to Expansion of Regulatory T Cells and Enhanced Susceptibility to Reinfection

Abstract: BALB/c mice are highly susceptible to experimental intraperitoneal Trypanosoma congolense infection. However, a recent report showed that these mice are relatively resistant to primary intradermal low-dose infection. Paradoxically, repeated low-dose intradermal infections predispose mice to enhanced susceptibility to an otherwise noninfectious dose challenge. Here, we explored the mechanisms responsible for this low-dose-induced susceptibility to subsequent low-dose challenge infection. We found that akin to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Moreover, intradermal infection discloses differences with the intraperitoneal route, as the mechanism of resistance to infection relies on a NO-and TNF-mediated innate immune response but does not require antibody, CD1d-restricted natural killer (NK) T cells, major histocompatibility complex (MHC) class II-restricted T cells, or regulatory T cells. Therefore, intradermal infection can contribute to vaccine failure and enhance susceptibility to reinfection by suppressing the adaptive protective immunity [41,48,86]. Skin myeloid cell heterogeneity is well recognized [87].…”
Section: Reviewmentioning
confidence: 98%
“…Moreover, intradermal infection discloses differences with the intraperitoneal route, as the mechanism of resistance to infection relies on a NO-and TNF-mediated innate immune response but does not require antibody, CD1d-restricted natural killer (NK) T cells, major histocompatibility complex (MHC) class II-restricted T cells, or regulatory T cells. Therefore, intradermal infection can contribute to vaccine failure and enhance susceptibility to reinfection by suppressing the adaptive protective immunity [41,48,86]. Skin myeloid cell heterogeneity is well recognized [87].…”
Section: Reviewmentioning
confidence: 98%
“…Therefore, it is likely that the intraperitoneal route of infection (as is used during most experimental infections) may not clearly represent the early immune response that occurs during natural infection when the vector bites their human or animal hosts (24). Indeed, it has been shown that intradermal infection of experimental animals is able to induce the activation of some immune mediators that are distinct from those seen during intraperitoneal infection (24, 25). Therefore, the use both the intradermal and intraperitoneal infection routes of infection (when possible) in experimental African trypanosomiasis would be helpful in comparing the immune responses due to different infection routes.…”
Section: Routes Of Infection In Experimental African Trypanosomiasismentioning
confidence: 99%
“…Alternatively, development of experimental therapies that leverage both innate and adaptive immune arms without illicit effect is more attractive [ 36 ]. While synergy between innate and adaptive immunity is expected to potentiate immunotherapeutic response, chronic inflammatory stimuli may stymie an effective adaptive response [ 37 40 ]. In preclinical studies, low-dose infection with intradermal Trypanosoma congolense mediated expansion of regulatory T cells [ 37 40 ].…”
Section: Initiating Innate Immunitymentioning
confidence: 99%
“…While synergy between innate and adaptive immunity is expected to potentiate immunotherapeutic response, chronic inflammatory stimuli may stymie an effective adaptive response [ 37 40 ]. In preclinical studies, low-dose infection with intradermal Trypanosoma congolense mediated expansion of regulatory T cells [ 37 40 ]. Similarly, as malignancies grow, they may precipitate similar levels of inflammation that predispose induction of regulatory cell subsets, which ultimately confound an appropriate adaptive response [ 34 , 41 , 42 ].…”
Section: Initiating Innate Immunitymentioning
confidence: 99%